Direct interaction of Vδ7 TCRs with IL17RA drives the differentiation of T H 1-like γδT cells - Kewei Ye; Nimmy Francis; Josefine Dunst; Amanda Borgenstam; Iris Rocamonde-Lago; Stefanie Köhler; Yuanyuan You; Anatoly Dubnovitsky; Anja Kramer; Fanxi Meng; Valentin Zollner; Lisa Vogg; et al. (Science, 2026)
Of the three classes of lymphocytes that constitute the adaptive immune system, γδT cells are the only class for which the principles of antigen recognition remain enigmatic. Although endogenous γδT cell antigen receptor (γδTCR) ligands are thought to regulate γδT cell development, their identities are largely elusive. Here, we identified the interleukin 17 receptor A chain (IL17RA) as a γδTCR ligand that drove the differentiation of Vδ7 + γδT cells with a T helper 1 (T H 1)–like effector program in mice. IL17RA promoted this differentiation through an interaction involving germline-encoded regions of the Vδ7 chain, enabling the selection of cells with a diverse CDR3 repertoire and thus acting as a nonclonotypic γδTCR ligand. Together with the nonclonotypic mode of γδTCR engagement by butyrophilins, these results suggest that such interactions represent a general biological mechanism shaping the γδT cell compartment.